2009
DOI: 10.2135/cropsci2008.05.0297
|View full text |Cite
|
Sign up to set email alerts
|

Downward Mobility of 14C‐Labeled Simazine in a Bermudagrass System vs. a Fallow Soil System

Abstract: Pesticides applied to bermudagrass (Cynodon dactylon L.) can be captured by the canopy, absorbed by the roots, or bound in the thatch layer, which reduces the amount available to leach compared with a fallow soil system where pesticides may be applied directly to soil. 14C‐Simazine was applied to dormant bermudagrass and fallow soil in lysimeters in a cold growth chamber (5°C) (cold‐fallow soil) and to actively growing bermudagrass and fallow soil in lysimeters in a greenhouse (25°C) (warm‐fallow soil) in Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It was concluded that perennial ryegrass may be safely reseeded two weeks after sulfosulfuron applications at 34 or 67 g a.i./ha, but creeping bentgrass and Kentucky bluegrass may require up to four weeks to safely reestablish in treated areas. Simazine is generally safe for actively growing bermudagrass, but soil residual activity may influence turf establishment (Lawson et al, 2002;Syngenta, 2008;Cummings et al, 2009). In Georgia, simazine applied at 1.1, 2.2, or 4.4 kg a.i./ha the day of centipedegrass seeding [Eremochloa ophiuroides (Munro) Hack.]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that perennial ryegrass may be safely reseeded two weeks after sulfosulfuron applications at 34 or 67 g a.i./ha, but creeping bentgrass and Kentucky bluegrass may require up to four weeks to safely reestablish in treated areas. Simazine is generally safe for actively growing bermudagrass, but soil residual activity may influence turf establishment (Lawson et al, 2002;Syngenta, 2008;Cummings et al, 2009). In Georgia, simazine applied at 1.1, 2.2, or 4.4 kg a.i./ha the day of centipedegrass seeding [Eremochloa ophiuroides (Munro) Hack.]…”
Section: Resultsmentioning
confidence: 99%
“…Simazine is a photosynthesis inhibitor used for controlling numerous grassy and broadleaf weeds and may be safely applied to established bermudagrass during spring greenup (Johnson, 1982;Tworkoski et al, 2000;Syngenta, 2008). Simazine is efficacious for postemergence weed control, but treatments may also have significant soil residual activity that may affect turfgrass seedling establishment (Tworkoski et al, 2000;Cummings et al, 2009;Hixson et al, 2009). Reseeding bermudagrass over areas once occupied by patches of weeds may be desirable following rimsulfuron, simazine, or sulfosulfuron treatments.…”
mentioning
confidence: 99%
“…The percentage of bound 14 C increased with the age of the turf, which had soil carbon contents of 16.6 mg kg −1 soil for 4-yr-old turf (52% bound), 24.5 mg kg −1 for 21-yr-old turf (70% bound), and 39.0 mg kg −1 for 99-yr-old turf (71% bound). In other work with 14 C-simazine, Cummings et al (2009) indicated that applied herbicide may have adsorbed to the rhizoplane of dormant bermudagrass roots. Grass roots are reported to have a CEC of 10 to 30 cmol c kg −1 and OM has 120 to 250 or more, with most (90-100%) being pH dependent (Carrow et al, 2001).…”
Section: Adsorptionmentioning
confidence: 95%
“…Organic ma er binds metals (Jeong et al, 2007), inorganic nutrients (Danneberger et al, 1984;Kaiser et al, 2008;Kang et al, 2009), pesticides (Hurto and Turgeon, 1979;Balogh and Anderson, 1992;Dell et al, 1994;Lickfeldt and Branham, 1995;Cisar and Snyder, 1996;Raturi et al, 1997Raturi et al, , 2003Wu et al, 2002;Cummings et al, 2009;Hixson et al, 2009;Magri and Haith, 2009), organic compounds (Shih, 2007), and compounds such as tetracycline (Gu and Karthikeyan, 2008). In turn, OM can also be bound to soil minerals such as clays (Zhang et al, 2008;Kothawala et al, 2009).…”
Section: Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation